2019
DOI: 10.4103/jfmpc.jfmpc_161_19
|View full text |Cite
|
Sign up to set email alerts
|

Guillain Barre syndrome with pulmonary tuberculosis: A case series from a tertiary care hospital

Abstract: Introduction: Guillain-Barre syndrome (GBS) is post-infectious autoimmune polyradiculopathy which characteristically presents with a monophasic illness with CSF albumino-cytological dissociation with partial or complete recovery. The incidence of GBS is about 1 to 2/100,000 per year.[ 1 ] Subtypes are described based on electrophysiological patterns, the most common being acute inflammatory demyelinating polyneuropathy (AIDP) and rarer ones being acute motor axonal neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…AIH is an uncommon cause of chronic liver disease and viral infections are known to trigger AIH [ 5 ]. Different viral and bacterial infections are known to trigger autoimmunity [ 6 , 7 ]. They are associated with different various rheumatological diseases [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AIH is an uncommon cause of chronic liver disease and viral infections are known to trigger AIH [ 5 ]. Different viral and bacterial infections are known to trigger autoimmunity [ 6 , 7 ]. They are associated with different various rheumatological diseases [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different viral and bacterial infections are known to trigger autoimmunity [ 6 , 7 ]. They are associated with different various rheumatological diseases [ 7 , 8 ]. HEV is classically associated with circulating liver-directed autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…3 The review of reported cases is mentioned in ►Table 1. [3][4][5][6][8][9][10] The most common clinical features of the presentation of GBS are ascending quadriparesis with areflexia or hyporeflexia, and few case reports showed sensory involvement. 4,8 According to the American Academy of Neurology, intravenous immunoglobulins (IVIG) are as effective as plasmapheresis for treating GBS.…”
Section: Discussionmentioning
confidence: 99%